An embarrassment of riches: The seduction of postfeminism in the academy - Liu, Helena (Organization (London, England), 2019)
Given critiques of postfeminism as a neoliberal and patriarchal discourse that has taken considerable tolls on professional life, its popularity in organisational practice seems out of place. This article explores the processes of postfeminism through an autoethnographic inquiry of my experiences working as a research fellow at a leadership research centre in Australia. In theorising from my narrative accounts as an early career scholar, I offer a view into the entangled processes of postfeminist knowledge production and my own making as a postfeminist subject. In doing so, I attempt to illustrate the seductive appeal of postfeminism as an ostensibly empowering process that ultimately preserves White elite class patriarchal power.